Estimasi Percepatan Tanah Maksimum Di Kota Manado Berdasarkan Modifikasi Persamaan Atenuasi - Stevi Anjelo Langitan; Heindrich Taunaumang; Sixtus Iwan Umboh; Sesar Prabu Dwi Sriyanto (Jurnal FisTa : Fisika dan Terapannya, 2022)
In analyzing the risk of an earthquake it is necessary to have parameters used, one of which is the maximum ground acceleration or Peak Ground Acceleration (PGA). Some data is not fully available on the accelerometer network. Therefore, the purpose of this study is to select an appropriate GMPE equation to estimate the PGA size in Manado City. The selection of the GMPE equation in this study considers the relative difference value and the correlation coefficient in the GMPE equation. Based on these results, the formulation of Kanno, et al. (2006) was chosen to be the initial GMPE equation in the Manado City area. The equation is modified to get an equation with new coefficients. From the results of this equation, it can be determined that the city of Manado often experiences any type of earthquake and also gets the mitigation that needs to be applied.